Comparison of Clinical Outcomes Between Second-and First-Generation Drug-Eluting Stents in Patients With Chronic Total Occlusion Lesion: A Meta-Analysis - Qiao, Xuan; Zhang, Wen-Jiao; Guo, Wen-Fen; Li, Yan; Liang, Xi-Ying; Wang, Zhi-Lu (Frontiers in Cardiovascular Medicine, 2021)
Background and Objectives: The second-generation drug-eluting stents have been used to treat chronic total occlusion lesion. However, there is limited evidence of the clinical outcomes that whether the second-generation drug-eluting stents is superior to first-generation ones in patients with chronic total occlusion lesion undergoing percutaneous coronary intervention. The study aimed to compare the differences in clinical outcomes between the two generations drug-eluting stents in patients with those by a meta-analysis. Methods: PubMed, Embase, the Cochrane library and Web of science databases were systemically searched before March, 2021. Randomized controlled trials and observational studies were included to compare the second-generation drug-eluting stents with the first-generation ones in patients with chronic total occlusion lesion undergoing percutaneous coronary intervention. The clinical outcomes were major adverse cardiac events (MACE), target vessel revascularization, myocardial infarction, all-cause death. Fixed effects models were used to calculate the odds ratio (OR) and 95% confidence interval (CI) of each clinical outcome. Sensitivity analysis was performed to detect potential sources of heterogeneity. Subgroup analyses were used to assess the differential effects. Results: The meta-analysis included eight studies involving 4583 patients with chronic total occlusion lesion undergoing percutaneous coronary intervention. Pooled analysis showed that the incidence of MACE (OR=0.68, 95%CI 0.54-0.85, P=0.0008), target vessel revascularization (OR=0.70, 95%CI 0.54-0.91, P=0.007), and myocardial infarction (OR=0.58, 95%CI 0.37-0.93, P=0.02) were lower in the second-generation drug-eluting stents compared with the first-generation ones. However, there was not difference in all-cause deaths between two drug-eluting stents (OR=0.67, 95%CI 0.45-1.01, P=0.05). Conclusions: The second-generation drug-eluting stents are associated with lower MACE, target vessel revascularization, and myocardial infarction compared with the first-generation ones in patients with chronic total occlusion lesion undergoing percutaneous coronary intervention. The results of this study can provide a reference for the selection of stents in patients with chronic total occlusion lesion. Further randomized controlled trials are needed to verify that the second-generation drug-eluting stents is superior to the first-generation ones in patients with chronic total occlusion (Registered by PROSPERO, CRD42020158406).